The role of Islamic banks in Qatar in financing the industrial sector between 2013-2018 - Ahmed Elmoughni, Mohamed; Fayze Elharche, Ahmed (Finance and Business Economies Review, 2020)
The Qatari industrial sector has witnessed a significant development during the past years, and it has been able to meet the market needs of goods and products. The Islamic banking sector in Qatar has also witnessed a significant development in assets, deposits and financing, and financing has grown in the years 2013-2018 at a CAGR of 9.2%. Islamic banks in their turn to finance the industrial sector using several forms. This study attempts to monitor this role to represent a qualitative addition by focusing on a practical case study, and identifying the reality of industrial sector financing, the challenges it faces, and ways to overcome it. To achieve this goal, the researcher followed the descriptive approach and the analytical approach, in addition to the qualitative approaches adopted in the analysis of interviews that This study was conducted with a number of finance officials in Islamic banks and experts in financing. This study concluded the positive role that Islamic finance contributes to the industrial sector. The study recommended a number of recommendations to develop the role of Islamic banks in Qatar and overcome challenges and obstacles in financing the industrial sector in Qatar.